Public willingness to pay for alternative management regimes of remote marine protected areas in the North Sea. (June 2016) - Brouwer, R.; Brouwer, S.; Eleveld, M.A.; Verbraak, M.; Wagtendonk, A.J.; van der Woerd, H.J.
Abstract: Despite increasing attention paid to the value of marine resources, in particular marine protected areas (MPAs), their economic valuation focuses mainly on use values of ecosystem services such as fishery and tourism. Furthermore, most MPA related studies are carried out for coastal ecosystems, especially tropical coral reefs. The valuation of remote marine ecosystems is rare. The main objective of this paper is to estimate public willingness to pay (WTP) for alternative management regimes of a network of offshore MPAs in the North Sea under the Marine Strategy Framework Directive (MSFD). In a baseline valuation study carried out just before the adoption of the MSFD, beach visitors and a random sample of coastal and non-coastal residents were asked for their preferences for two alternative management options of three remote, ecologically sensitive areas with multiple use conflicts. Despite the lack of public awareness and familiarity with the offshore marine areas, a majority of 70% is willing to pay extra tax for their protection. Using a conservative value elicitation procedure, Dutch households are willing to pay on average maximum 0.25% of their annual disposable income to ban access and economic use. This serves as an indicator of what a network of remote MPAs in the MSFD is allowed to cost according to the Dutch tax payer. Highlights: Policy demand for the economic value of marine protected areas (MPAs) is increasing. The valuation of the non-market benefits of remote offshore MPAs worldwide is rare. Public willingness to pay (WTP) is estimated for a network of MPAs in the North Sea. Dutch households' WTP to ban access and use is 0.25% of their disposable income. This gives important indications what the network of MPAs can cost under the MSFD.